Results of Indoor Propagation Measurement Campaign at 1900 MHz - Pechač, Pavel; Klepal, M.; Zvanovec, S. (Radioengineering Society, 2001)
For the design of indoor picocellular systems in the frequency band of 1800/2100 MHz, a signal propagation modelling is needed. Empirical and semi-empirical models represent an efficient approach to the coverage prediction. For these models, suitable empirical parameters must be provided. The indoor propagation measurement campaign in the frequency range of 1900 MHz was carried out in several multi-floored buildings in Prague and Brno . For the campaign a special portable measurement system was developed. Based on the measurement results, the model parameters were derived. Optimised parameters are presented for two basic models (empirical and semi-empirical) according to the indoor environment classification. The results are compared to standard models as well. Accuracy and validity of derived models are discussed.
Keywords: Measurement; indoor propagation prediction; electro-magnetic waves; PCS